2016
DOI: 10.1182/blood-2015-08-664656
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent Fc receptor blockade by an anti–Fcγ receptor/albumin fusion protein ameliorates murine ITP with abrogated toxicity

Abstract: Key Points We generated a novel monovalent anti-FcγRIII/albumin fusion protein that ameliorates antibody-mediated murine ITP. Severe adverse events by anti-FcγR antibodies because of FcγR cross-linking are overcome by monovalent FcγR blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“…To explore the relative contribution of particular FcγRs to the function of the anti-CTLA-4 hIgG1 mAb, we utilized a panel of mAb reagents to selectively block individual FcγR-Fc interactions (Figures 4B and S4E) (Veri et al, 2007; Yu et al, 2016). Remarkably, only blockade of the FcγRIIIA-hIgG1 interaction significantly reduced anti-CTLA-4 mAb-induced T cell IL-2 responses.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the relative contribution of particular FcγRs to the function of the anti-CTLA-4 hIgG1 mAb, we utilized a panel of mAb reagents to selectively block individual FcγR-Fc interactions (Figures 4B and S4E) (Veri et al, 2007; Yu et al, 2016). Remarkably, only blockade of the FcγRIIIA-hIgG1 interaction significantly reduced anti-CTLA-4 mAb-induced T cell IL-2 responses.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was supported by a study using a passive ITP mouse model in which a monovalent anti-FcγRIII antibody was used. This construct which blocks immune complex-mediated engagement of FcγRIII mediated an efficient inhibition of antibody-dependent platelet removal without triggering adverse events (339). …”
Section: Autoantibody-induced Cell Lysis: Idiopathic Thrombocytopenicmentioning
confidence: 99%
“…The increased platelet clearance arises through diverse mechanisms, such as antiplatelet autoantibodies production, and T lymphocyte dysfunction. It was reported that receptors for the Fc fragment of IgG result in the removal of platelets coated with immunoglobulin ( 1 ) and the activation of phagocytosis in the reticuloendothelial system ( 2 ). In addition to B cell dependent autoimmune mechanisms, it is well established that cellular immune pathophysiology of ITP is associated with several T-cell abnormalities, including uncontrolled activation of T helper cells, deficiency of T regulatory cells, and increase of CD8 + T cell targeting megakaryocytes, etc.…”
Section: Introductionmentioning
confidence: 99%